2021
DOI: 10.23887/jptk-undiksha.v18i1.32376
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality for Supporting Authentic Learning in 21st Century Language Classroom

Abstract: Pembelajaran otentik adalah konsep untuk mendekatkan dunia nyata atau pengalaman nyata kepada siswa di dalam kelas. Penggunaan pembelajaran otentik yang menghadirkan realitas di dalam kelas lebih kontekstual dengan aktivitas siswa sehari-hari. Virtual Reality (VR) menawarkan simulasi multimedia 3D kehidupan nyata interaktif, mempromosikan interaktivitas dengan dunia ciptaan, dan memungkinkan sensasi sensorik. Artikel ini mensintesis artikel penelitian sebelumnya dari jurnal terindeks SCOPUS tentang penggunaan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Virtual Reality can bring reality to the classroom because of the environment in which Virtual Reality can be built. Related to the increasingly widespread use of Virtual Reality in the 21st century (Utami, Suwastini, Dantes, Suprihatin, & Adnyani, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual Reality can bring reality to the classroom because of the environment in which Virtual Reality can be built. Related to the increasingly widespread use of Virtual Reality in the 21st century (Utami, Suwastini, Dantes, Suprihatin, & Adnyani, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among them the research conducted by (Dharma et al, 2018) on early childhood (PAUD) who found that there was an effect of using virtual reality media on student learning outcomes. Other researchers have revealed that the use of virtual reality provides several benefits in authentic learning in 21st century language classes (Utami et al, 2021); (Andre, Handriyantini, & Oktavia, 2019) in their research conclusion stated that virtual reality technology can be implemented into an educational game on the android platform by using Unity 3D as the game engine.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential in areas where English is not part of the daily interaction, such as rural and frontier areas. Indonesia has a broad coverage of such regions, where books are rare, and internet connections are scarce (Puspitasari, Suwastini, Blangsinga, Dantes, & Tuerah, 2021;Utami, Suwastini, Dantes, Suprihatin, & Adnyani, 2021). In such a situation, reading aloud can be very practical for honing children's listening skills and getting them accustomed to hearing English words.…”
Section: Reading Aloud For Training Listening Skillsmentioning
confidence: 99%
“…One of the commonly used learning modalities is the visual modality. It is closely related to the audiovisual trend that affects a lot of students to enjoy visual audio and visual stimuli better than textual ones (Ariantini, Suwastini, Adnyani, Dantes, & Jayantini, 2021;Hutapea & Suwastini, A 2019;Listiani, Suwastini, Dantes, Adnyani, & Jayantini, 2021;Puspawati, Suwastini, Hutapea, Dantes, & Adnyani, 2021;Suwastini, Dantes, Jayanta, & Suprihatin, 2020;Suwastini, Lasmawan, Artini, & Mahayanti, 2020;Suwastini, Utami, & Artini, 2020;Utami, Suwastini, Dantes, Suprihatin, & Adnyani, 2021).…”
Section: A Introductionmentioning
confidence: 99%